Pengaruh Coping Mechanism Terhadap Psychological Well-Being Pada Mahasiswa - Sesarelia, Audy Najwa; Arsyad, Muhammad; Putro, Hendro Yulius Suryo (Jurnal Bimbingan dan Konseling Ar-Rahman, 2024)
The situation in university raises several problems for students and tends to make it difficult for them to adapt, thus hindering their development as individuals. The more problems there are, the lower the level of students' psychological well-being. This encourages students to carry out strategies to overcome problems, which are called coping mechanisms. This research aims to find out how much influence coping mechanisms have on the psychological well-being of the 2021 class of FKIP ULM students. The research approach uses a quantitative approach with a type of expost-facto research. Data collection tools were the Coping Mechanism Scales questionnaire and Ryff's Scales of Psychological Well-Being. Sampling used simple random sampling with the research sample, namely 310 students from the 2021 class of FKIP ULM. Data analysis techniques use descriptive statistics and simple linear regression. The research results show that students' coping mechanisms are classified as high and students' psychological well-being is classified as moderate. From simple linear regression calculations, the R Square result was 43.8%, which is classified as moderate (sig = 0.001). The influence of coping mechanisms on psychological well-being is very significant, so that the level of psychological well-being of students can be seen from how coping strategies are carried out, because coping mechanisms are said to be quite influential predictors.___________________________________________________________________Situasi di perguruan tinggi memunculkan beberapa masalah pada mahasiswa dan cenderung membuat mereka kesulitan dalam menyesuaikan diri, sehingga menghambat pengembangan diri sebagai pribadi. Semakin banyak masalah, maka semakin menurun pula tingkat kesejahteraan psikologis mahasiswa. Hal tersebut mendorong mahasiswa untuk melakukan strategi dalam mengatasi permasalahan, yang disebut dengan coping mechanism. Penelitian ini bertujuan untuk mencari tahu seberapa besar pengaruh coping mechanism terhadap psychological well-being pada mahasiswa angkatan 2021 FKIP ULM. Pendekatan penelitian menggunakan pendekatan kuantitatif dengan jenis penelitian expost-facto. Alat pengumpulan data adalah angket Coping Mechanism Scales dan Ryff’s Scales of Psychological Well-Being. Penarikan sampel menggunakan simple random sampling dengan sampel penelitian yaitu mahasiswa angkatan 2021 FKIP ULM sebanyak 310 orang. Teknik analisis data menggunakan statistik deskriptif dan regresi linear sederhana. Hasil penelitian menunjukkan bahwa coping mechanism mahasiswa tergolong tinggi dan psychological well-being mahasiswa tergolong sedang. Dari perhitungan regresi linear sederhana didapatkan hasil R Square sebesar 43,8% yang tergolong sedang (sig = 0,001). Pengaruh coping mechanism terhadap psychological well-being sangat signifikan, sehingga tingkat psychological well-being mahasiswa dapat dilihat dari bagaimana strategi coping yang dilakukan, karena coping mechanism disebut sebagai prediktor yang cukup berpengaruh.